A STUDY ON FACTORS INFLUENCING LEADERSHIP STYLES AND PRACTICES IN LIFE INSURANCE INDUSTRY - Dr.R.Sridharan , Dr.M.Hemanathan , Dr.S.Chitra (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The Indian life insurance industry has its own origin and history, since its inception. It has passed through many obstacles and hindrances to attain the present status. Insurance owes its existence to 17th century England. In fact, it took shapes in 1688 at a rather interesting place called Lloyd's Coffee House in London, where merchants, ship-owners and underwriters met to discuss and transact business. This research paper is an attempt to focus on the study of Leadership styles in Life Insurance Industry and also to find out the effectiveness of Leadership on the overall performance of the organization as well as development of the employees. The research work ends with certain useful recommendations to make the prevailing leadership styles more effective and contributory for micro and macro development of insurance sector.